An experiment for regulatory policy on broadband speed advertising - Shane Timmons; Terence J. McElvaney; Pete Lunn (The Economic and Social Research Institute (ESRI), 2019)
Identifying whether hyperbolic advertising claims influence consumers is important for consumer protection, but differentiating mere "puffery" from misleading advertising is not straightforward. We conducted a pre-registered experiment to determine whether pseudo-technical advertising claims about broadband speed bias consumer choice. We tested whether these claims lead consumers to (i) make suboptimal choices and (ii) choose faster, more expensive broadband packages than they otherwise would. We also tested a potential policy response, consisting of consumer information on broadband speeds and how they are advertised. One-in-five consumers chose a provider advertising "lightning fast" broadband over another offering the same speed at a cheaper price. Puffery also led consumers to choose faster, more expensive packages than consumers who saw no such claims. The information intervention (i) decreased the proportion of suboptimal decisions, (ii) increased the likelihood that consumers switched package, and (iii) improved understanding of speed descriptions. The findings suggest that a relatively soft regulatory intervention may benefit broadband consumers.
Keywords: D12; D18; D83; D90; M37; M38; 330; decision-making; behavioural economics; consumer protection; telecommunications